#TITLE_ALTERNATIVE# - MEUTIA (NIM 10104049), NAFIRA
Insurance industry, especially car insurance, is one of the financial service businesses that has grown rapidly. In this present work, data on reported claims in a car insurance business was analyzed. Analysis was carried out using a binary logit model with the assumption that the probability of claims reported in a particular age of policy in one policy year depends on gender and total sum insured. The effect of gender and total sum insured on the probability of claims reported was analyzed in: the first month of the policy period; the last month of the policy period; and the first six months of the policy period. A study was also carried out to analyze the effect of gender and total sum insured on the probability of more than one claim reported in one period. The results showed that with 10% level of significance (alpha ), total sum insured gives significant effect to the probability of claims to be reported in the first month of the policy period; while gender significantly affects the probability of more than one claim is reported in one period.